The Influence of Social Media and Brand Awareness on Willingness to Pay Premium Price with Green Attitude as a Mediating Variable on Gen Z Users of Green Product Tupperware Drinking Bottles in East Jakarta City - Riswan, Muhammad Syahendra; Wijayanto, Andi; Farida, Naili (Journal Research of Social Science, Economics, and Management, 2025)
Awareness of environmentally friendly products has become a crucial issue in line with growing global attention to resource efficiency and environmental impact reduction. Generation Z, as young consumers, tends to have high environmental concerns, which may influence their willingness to pay a premium price for green products such as Tupperware bottles. This study applied a quantitative approach using questionnaires distributed to 100 Gen Z respondents who use Tupperware in East Jakarta. The data were analyzed using Structural Equation Modeling with the Partial Least Square (SEM-PLS) method. The findings reveal that social media has a positive and significant effect on both willingness to pay a premium price and green attitude. Brand awareness also significantly and positively affects these two variables. Moreover, green attitude significantly influences willingness to pay a premium price and mediates the relationship between social media and willingness to pay a premium price as well as between brand awareness and willingness to pay a premium price. These findings highlight that communication strategies through social media and strengthening brand awareness are effective in shaping Gen Z's green attitude. A positive environmental attitude increases their willingness to pay a premium price for eco-friendly products. This provides valuable insight for companies in developing sustainable marketing strategies targeting young consumers.